2018
DOI: 10.1002/jcp.26321
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism by which Astragalus polysaccharide protects against ROS toxicity through inhibiting the protein dephosphorylation of boar sperm preserved at 4 °C

Abstract: Numerous studies have shown that Astragalus polysaccharide (APS) has strong antioxidant effects and high practical value for preserving semen at low temperatures in vitro. However, to date, little attention has been paid to the precise mechanism of APS in sperm preservation at 4 °C. Thus, to gain further insight into the protective effects of APS, the present study was performed to assess the changes in sperm quality parameters, antioxidant capacity, ATP content, and protein phosphorylation levels. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Several studies have reported that ROSspecific inhibitor effectively alleviated cisplatin-induced kidney toxicity by reducing ROS accumulation [35]. APS has been reported to be a natural antioxidant in various pathological states [14,18,36,37]. As anticipated, in our study, APS also could mitigate cisplatin-induced oxidative damage by reducing ROS generation and recovering the activities of T-SOD and GSH-Px.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have reported that ROSspecific inhibitor effectively alleviated cisplatin-induced kidney toxicity by reducing ROS accumulation [35]. APS has been reported to be a natural antioxidant in various pathological states [14,18,36,37]. As anticipated, in our study, APS also could mitigate cisplatin-induced oxidative damage by reducing ROS generation and recovering the activities of T-SOD and GSH-Px.…”
Section: Discussionsupporting
confidence: 84%
“…It results from high concentrations of free radicals and suppression of antioxidant potential, which may alter protein expression in spermatozoa [14]. The positive effects of Astragalus polysaccharide on boar sperm quality were mainly due to the elimination of excessive mitochondrial ROS, the improvement of antioxidant capacities and the enhancement of ATP levels [15]. Feeding diet with 500 mg/kg oregano essential oil may resulted in decrease in sperm ROS [16].…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of 10% β-mercaptoethanol were added to the samples, and the resulting sample mixture was boiled again for 3 min. The extracted sperm proteins were quantified by spectrophotometry (NanoDrop 2000, Thermo Scientific, USA) [27]. The extracted sperm proteins were resolved by SDS-PAGE.…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%